Influence of pinching and plant growth regulators on flowering, yield and economics of fenugreek (Trigonella foenum-graecum L.) - A L N Prasad, V Krishnaveni, T Padmalatha, S S V (Journal of Spices and Aromatic Crops, 2016)
A field experiment was conducted to evaluate the effect of pinching and plant growth regulators on flowering and seed yield of fenugreek cv. APHU Methi-1. Minimum time to 50% flowering and seed maturity and maximum test weight were recorded with no pinching (P0) treatment. Single pinching at 25 days after sowing (DAS) (P1) recorded significantly maximum number of pods, length of pod, number of seeds pod-1 and seed yield. Among the plant growth regulators, foliar spray of GA3 50 ppm (G1) thrice (25, 45 and 65 DAS) resulted in best performance of the yield parameters like number of pods plant-1, length of pod, number of seeds pod-1 and seed yield plant-1. Early flower initiation and early maturity was observed with application of GA3 75 ppm (G2). Among the interactions of pinching and plant growth regulators (PGRs), the treatment combination of no pinching with application of GA3 50 ppm (P0G1) resulted in maximum test weight. Maximum yield attributes like number of pods plant-1, length of pod and seed yield plant-1 were recorded with single pinching at 25 DAS and application of GA3 50 ppm (P1G1). However, pinching at 25 DAS with application of NAA 50 ppm (P1G3) gave highest B: C ratio (1.88).